Autonomic Modulation in Different Phases of Menstrual Cycle in Younger and Older Indian Women - Bindiya Sathish; Bhat, Ramesh; Damodara Gowda K M (International Journal of Medical Research, 2013)
Background: The menstrual cycle is an integral part of a major portion of a woman’s life, associated with significant changes in multiple neurohumoral homeostatic mechanisms. In the present study, autonomic modulation in different phases of menstrual cycle in young adult and older adult women’s was assessed. Methods: About 90 subjects were recruited and were divided between 2 groups and their HRV was recorded in 3different phases and compared between young adults and older adult women. The HRV evaluation was done in the frequency domain using the software Version1.1, AIIMS, New-Delhi. The data was analyzed using students‘t’ test followed by Mann Whitney-U test and P< 0.05 was considered the level of significance. Result: HRV was analyzed using LF in three phases of menstrual cycle in two sub groups did not show any significant variations. In HF Component in Group-I when compared the menstrual with follicular, luteal phases, the menstrual phase showed significantly higher values. Comparison of LF/HF ratio between menstrual and follicular phase in Group-I showed significantly high variation between menstrual and luteal phases. Conclusion: We conclude that a slow and steady decline in autonomic modulation with age, may have a close interaction with hormonal activity.